2024
DOI: 10.1039/d3ey00247k
|View full text |Cite
|
Sign up to set email alerts
|

Direct biomass valorisation to γ-valerolactone by Ru-PNP catalysed hydrogenation in acid

Sakhitha Koranchalil,
Martin Nielsen

Abstract: Converting carbohydrate-rich biomass waste directly to γ-valerolactone (GVL) is highly attractive but challenging owing to the inert nature and high complexity of biomass, necessitating a versatile and selective catalytic system....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Using directly carbohydrate-rich biomass waste as feedstock, Koranchalil and Nielsen have associated the formation of insoluble humins to the diminished activity and the low yields to GVL obtained using the homogeneous Ru-MACHO-BH catalysts in aqueous H 3 PO 4 , which are favoured under higher H 3 PO 4 acid concentration and higher temperature [92]. They speculate that humins are formed to a greater extent in the more concentrated samples [93].…”
Section: Catalyst Deactivation By Carbonaceous Species (Humins and Co...mentioning
confidence: 99%
“…Using directly carbohydrate-rich biomass waste as feedstock, Koranchalil and Nielsen have associated the formation of insoluble humins to the diminished activity and the low yields to GVL obtained using the homogeneous Ru-MACHO-BH catalysts in aqueous H 3 PO 4 , which are favoured under higher H 3 PO 4 acid concentration and higher temperature [92]. They speculate that humins are formed to a greater extent in the more concentrated samples [93].…”
Section: Catalyst Deactivation By Carbonaceous Species (Humins and Co...mentioning
confidence: 99%
“…[34] Recently, we demonstrated that Ru-MACHO-BH is also an active hydrogenation catalyst under acidic conditions for the direct transformation of carbohydrates and raw biomass to GVL. [35] Herein, we show the activity of PNP pincer complex in acidic medium (H 3 PO 4 ) for the direct synthesis of GVL from furfural through a one-pot sequence of hydrogenation, hydrolysis, a second hydrogenation, and finally a lactonization (Scheme 1). Showing that furfural is a viable substrate for GVL production under acidic conditions using homogeneous catalysis demonstrates that hemicellulose is also a feasible substrate for this approach using similar conditions.…”
Section: Introductionmentioning
confidence: 99%